Processos poéticopedagógicos na criação do espetáculo de dança sopro - Gomes, Letícia Nascimento (2015)
This dissertation aims to show how it is the presentification of the scenic direction in dance on the creative process of Acasos Dance Company's spectacle, Sopro, of 2014. This is done through the poeticpedagogical processes, situated as the strategies and ways of working that have been used in the construction of this spectacle from from a collective direction format.To this end it was held monitoring of the creative process of Sopro with strategies and instruments of the ethnographic method as the interview and participant observation. This added to the feature of being a work in which the researcher is involved in the search field, enhances the adoption of autobiographical tone thought from the Autoetnografia.To position the poeticpedagogical processes as agents of direction's presence in dance and the will of contact with the things of the world that accompanies the Sopro spectacle, it was used the understanding of Production of presence of Gumbrecht (2010).It is expected that the collective direction can be thought in a pedagogy of expression through poeticpedagogical processes, which put into evidence a dance pedagogy, that occurs in the making with powerful creative possibilities and developments of trading relations and of acquaintanceship in a collectivity.And that way, could be tried in other scenery- not only in independent dance companies as Acasos - but in other artistic works or even in a formal education.